2013
DOI: 10.1371/journal.pone.0068929
|View full text |Cite
|
Sign up to set email alerts
|

Blood Viscosity and the Expression of Inflammatory and Adhesion Markers in Homozygous Sickle Cell Disease Subjects with Chronic Leg Ulcers

Abstract: ObjectiveTo determine differences in TNF-α, IL-1β, IL-10, sICAM-1 concentrations, leg hypoxia and whole blood viscosity (WBV) at shear rates of 46 sec-1 and 230 sec-1 in persons with homozygous S sickle cell disease (SCD) with and without chronic leg ulceration and in AA genotype controls.Design & Methods: fifty-five age-matched participants were recruited into the study: 31 SS subjects without leg ulcers (SSn), 24 SS subjects with leg ulcers (SSu) and 18 AA controls. Haematological indices were measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 53 publications
3
38
1
Order By: Relevance
“…Elevated levels of fetal hemoglobin are generally protective [9,29,41], although this has not been true in all studies [33,42]. SCD ulcer patients have higher levels of soluble ICAM-1 and the key inflammatory cytokine IL-1beta [43]. We have found that the active ulcer and peri-ulcer area have higher blood flow than distant, non-ulcerated areas of the leg, are characterized histopathologically by venostasis, inflammation, and vasculopathy, with activated endothelium and evidence of thrombosis/recanalization (Figs.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Elevated levels of fetal hemoglobin are generally protective [9,29,41], although this has not been true in all studies [33,42]. SCD ulcer patients have higher levels of soluble ICAM-1 and the key inflammatory cytokine IL-1beta [43]. We have found that the active ulcer and peri-ulcer area have higher blood flow than distant, non-ulcerated areas of the leg, are characterized histopathologically by venostasis, inflammation, and vasculopathy, with activated endothelium and evidence of thrombosis/recanalization (Figs.…”
Section: Pathophysiologymentioning
confidence: 99%
“…2,7 Etiologic factors include the sickling of red blood cells in blood vessels, causing vaso-occlusion and impairing oxygen delivery to tissues; as well as the binding of hemolysis-freed hemoglobin to nitric oxide, deactivating it and subsequently resulting in vasoconstriction. 1,8,11 Blood viscosity and inflammatory factors are also being studied to determine whether these are increased in patients manifesting chronic leg ulcers and whether they have an impact on the development of ulcer. Recent evidence also indicates that there is an element of venous incompetence in sickle cell patients.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Recent evidence also indicates that there is an element of venous incompetence in sickle cell patients. 1,2,8 All the earlier mechanisms can either occur spontaneously in a patient with SCD, or alternatively be caused by trauma, which may start a cascade of the aforementioned mechanisms, leading to ulcer formation.…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations